CONFLICTS OF LEGAL NORMS AND THE IMPLICATIONS OF LAND EXECUTION VIEWED FROM KARL MARX'S THEORY - Nur Huda; Hufron (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Execution (forced eviction) is the final course of action taken when the losing party in a case refuses to comply with a court decision. This measure carries complex consequences, ranging from the loss of residence and livelihood to psychological impacts and the erosion of social and cultural identity. The magnitude of such losses often drives affected parties to struggle for their rights, as exemplified by the residents of Pulosari, Gunungsari Subdistrict, Dukuh Pakis District, Surabaya City, whose homes were forcibly vacated by the Surabaya District Court upon the petition for eviction execution filed by PT Patra Jasa in 2018, based on Decision No. 333/Pdt.G/2013/PN.Sby, dated January 21, 2014. The objective of this study is to examine the existence of a norm conflict in the issuance and implementation of the said eviction order. This research adopts a normative legal methodology, which analyzes the application of legal norms and their social impacts. The research approach used is descriptive-qualitative. The findings indicate that a conflict of norms exists within the Surabaya District Court’s decision (No. 333/Pdt.G/2013/PN.Sby, dated January 21, 2014), which serves as the basis for the execution of eviction. The conflict arises between Article 178 of the Herziene Indonesisch Reglement (HIR) and Law No. 48 of 2009 on Judicial Power. Article 178 HIR prohibits judges from deciding beyond what is demanded (ultra petita), whereas Law No. 48 of 2009 grants judges interpretive discretion in applying legal rules, thereby allowing the issuance of an execution order that diverges from the operative part (dispositif) of the decision. The issuance of an execution order inconsistent with the original ruling reflects a conflict between judicial norms and administrative norms. This condition aligns with Karl Marx’s theory of law, which posits that law functions as an instrument of interest for the ruling or propertied class.